2005
DOI: 10.4269/ajtmh.2005.73.753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Program to Eliminate Lymphatic Filariasis in Vanuatu Following Two Years of Mass Drug Administration Implementation: Results and Methodologic Approach

Abstract: This report presents the results of the Vanuatu mid-term evaluation of the lymphatic filariasis elimination program being implemented countrywide. Vanuatu is one of the first countries to initiate this program as part of the Global Program for Elimination of Lymphatic Filariasis, based on a five-year annual mass drug administration (MDA) of albendazole and diethylcarbamazine and complemented in Vanuatu by extensive coverage with bed nets. This paper reports results of 561 persons tested at eight sentinel sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
(14 reference statements)
0
27
1
Order By: Relevance
“…Moreover, in India after six rounds of MDA, the coverage was only 54 -75% of the eligible population, 9 and in Vanuatu the MDA coverage after two years was 72%. 10 Reported MDA coverage rates were around 45% in Ghana and Kenya. 11 Males reported higher MDA compliance than females in our study, and this finding is consistent with results reported from Haiti, where compliance was 77.7% in males and 54% in females.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in India after six rounds of MDA, the coverage was only 54 -75% of the eligible population, 9 and in Vanuatu the MDA coverage after two years was 72%. 10 Reported MDA coverage rates were around 45% in Ghana and Kenya. 11 Males reported higher MDA compliance than females in our study, and this finding is consistent with results reported from Haiti, where compliance was 77.7% in males and 54% in females.…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel site B surveys were started in eight villages in 2002 [12]. Spot-check site surveys were also initiated in several villages and hospitals between 2002 and 2004 during the MDA period [4].…”
Section: Methodsmentioning
confidence: 99%
“…These sites were Sola and Mosina Village (Torba Province), Sakau and Wanur villages (Penama Province), Orap and Unmet villages (Malampa Province), and Port Resolution and South River villages (Tafea Province) [14]. In 2002, after two rounds of MDA, the B survey was conducted to evaluate whether MDA was decreasing antigen prevalence in these villages of high endemicity [14]. All individuals >10 years were invited to have an ICT blood test (except in Port Resolution where only 300 were examined).…”
Section: Methodsmentioning
confidence: 99%
“…This is the first published paper presenting comprehensive results of Vanuatu’s LF Control Program, building on Fraser et al’s (2005) evaluation of mid-term results [14]. This paper describes LF prevalence before MDA, results from sentinel site and spot check surveys during MDA, and LF prevalence after 5 years of MDA.…”
Section: Introductionmentioning
confidence: 99%